Comparison between common models of forces on oar blades and forces measured by towing tank tests - Barre, S.; Kobus, J.-M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
This paper describes the hydrodynamic forces on oar blades and compares measured data with common models: one model using a normal force coefficient and the other using drag and lift coefficients. The data were obtained from tests in towing tanks on blades at reduced scale (typically 0.7). The measurement device can reproduce oar movements and measure the six components of the hydrodynamic efforts. These tests provide a better control, precision, and repeatability than measurements on water. The experimental modelling leads to defining the oar strokes using only the maximum rotation rate and an advance number, which can also be defined as basic efficiency. These movements are simplified but remain representative of the main characteristics of the unsteady working of oars. The measurements show how the direction and zero-torque point influence instantaneous efficiency. They also show that the force evolution can be described using the maximum values of drag and lift coefficients. These depend on the unsteadiness, characterized by a parameter equal to the difference between the velocities of the two blade edges divided by the normal component of the velocity of the blade centre. This parameter, fully related to the advance number, can be considered as a reduced frequency